Perilaku Laki-Laki Feminin, Dampak, Serta Penanganannya ( Studi Kasus di SMPN 33 Makassar) - Novianti Sudirman; Abdullah Sinring; M. Amirullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify forms of feminine male behavior in adolescents, analyze the causes and impacts, and test the effectiveness of treatment using the Choice Reality Therapy approach. This study used a case study method with a male student with the initials MFA at SMPN 33 Makassar as the subject. Data were collected through interviews, observations, and individual counseling interventions. The results showed that the subject's feminine behavior was manifested through the use of cosmetics (lip tint and skincare), the use of accessories, and a graceful gait. The main factor causing this behavior was the absence of a father figure (fatherlessness) since childhood, which triggered the subject to model and identify with his mother's gentle behavior. The consequences of this behavior were very significant, namely the subject became the target of verbal bullying (taunted as "sissy"). Experienced social exclusion, and psychological impacts such as feelings of shame, inferiority, and anxiety. Intervention with Reality Counseling through the WDEP (Wants, Doing, Evaluation, Plan) stages proved effective in handling this case. This approach successfully fostered self-awareness and personal responsibility in subjects to evaluate their behavior and develop more realistic and adaptive action plans. This success indicates that Reality Counseling is a relevant strategy for helping adolescents with non-conventional gender expressions achieve healthier adjustment. Keywords: Feminine Behavior, Fatherless, Bullying, Reality Counseling, SMPN 33 Makassar